Policy predictions if the model doesn't fit - Marco Del Negro; Frank Schorfheide (Federal Reserve Bank of Atlanta, 2004)
This paper uses a novel method for conducting policy analysis with potentially misspecified DSGE models (Del Negro and Schorfheide 2004) and applies it to a simple New Keynesian DSGE model. We illustrate the sensitivity of the results to assumptions on the policy invariance of model misspecifications.
Keywords: 330; Dynamisches Gleichgewicht; Modellierung; Bayes-Statistik; Theorie